Current Distribution of the Invasive Kelp Undaria pinnatifida (Harvey) Suringar, 1873 Along Artificial and Natural Habitats in North Portugal—Impacts and Mitigation Initiatives - Marcos Rubal; Jesús Fernández-Gutiérrez; Diego Carreira-Flores; Pedro T. Gomes; Puri Veiga (Plants, 2025)
The kelp Undaria pinnatifida is considered one of the 100 worst invasive species in the world. The presence of Undaria in Portugal was reported more than 20 years ago, but there is not recent detailed information about its distribution and impacts. The aims of this study are to provide updated data about the distribution of Undaria in marinas and natural habitats along the north Portuguese coast, to afford insights about Undaria impacts on native macroalgae and to test the efficiency of mitigation actions based on Undaria removal. Mitigation measures were implemented in a marina where a native kelp was recently displaced by Undaria. The results showed stable populations of Undaria in marinas, but few ephemeral ones on natural rocky shores. The observed distribution pattern suggests an important role of salinity and wave exposure in shaping the distribution of Undaria. Moreover, Undaria was able to displace a native kelp and overgrow mussels in marinas, while on natural rocky shores, it was able to overgrow Gongolaria baccata but not native kelps. Finally, mitigation actions resulted in a partial recolonization by the native kelp.